MANAJEMEN KINERJA - Soimah, Sri; Rahmah, Fatiyatur; Machdum Bachtiar (STKIP Subang, 2026)
This study aims to analyze performance management as a systematic and continuous process in achieving organizational goals effectively and efficiently. Performance management encompasses several stages, including goal and standard setting, planning, organizing, monitoring, evaluation, and the development of individual and team performance. The method used in this research is a library research approach with a descriptive qualitative design through the review of books, scientific journals, and relevant documents in the field of human resource management. The results of the study indicate that the success of performance management is largely determined by the clarity of goals that are measurable, realistic, and participatory, as well as their alignment with the organization’s vision and mission. Well-structured planning supported by needs analysis and appropriate resource allocation enhances work effectiveness. Continuous performance monitoring through clear indicators and the utilization of digital technology enables organizations to make timely and accurate adjustments. Performance evaluation plays a crucial role in assessing achievement levels, identifying strengths and weaknesses, and serving as a basis for strategic decision-making. Furthermore, performance development through training, coaching, and career planning is essential in improving competencies and closing performance gaps. Therefore, performance management functions not only as a control mechanism but also as a strategic instrument to enhance productivity, competitiveness, and organizational sustainability in the digital era.